High Hip Center Technique in Total Hip Arthroplasty for Crowe Type II–III Developmental Dysplasia: Results of Midterm Follow‐up. Issue 4 (9th August 2020) - Shen, Junmin; Sun, Jingyang; Ma, Haiyang; Du, Yinqiao; Li, Tiejian; Zhou, Yonggang
Abstract : Objectives: We aimed to show the utility of high hip center technique used in patients with Crowe II–III developmental dysplasia of the hip at the midterm follow‐up and evaluated the clinical and radiographic results between different heights of hip center. Methods: From December 2003 to November 2013, we retrospectively evaluated 69 patients (85 hips) with Crowe II–III dysplasia who underwent a high hip center cementless total hip arthroplasty. The patients were divided into two groups according to the height of hip center, respectively group A (≥ 22 mm and < 28 mm) and group B (≥28 mm). The survivorship outcomes and radiographic and clinical results, including the vertical and horizontal distances of hip center, femoral offset, abductor lever arm, cup inclination, leg length discrepancy, Trendelenburg sign, and limp were evaluated. Results: The mean follow‐up time was 8.9 ± 1.8 years. The mean location of the hip center from the inter‐teardrop was 25.1 ± 1.6 mm vertically and 30.0 ± 3.8 mm horizontally in group A, and 33.1 ± 4.8 mm vertically and 31.4 ± 6.1 mm horizontally in group B. Eleven hips of group B showed a lateralization over 10 mm, and the same was shown in one hip in group A ( P = 0.012). There were no statistically significant differences between two groups in postoperative femoral offset, abductor lever arm, leg length discrepancy and cup inclination. At the final follow up, the mean WOMAC and Harris hip score were significantly improved in both groups. Of the 85 hips, four hips in group A and three hips in group B showed a positive Trendelenburg sign. Additionally, four patients in group A and two patients in group B presented with a limp. No significant differences were shown regarding the Harris hip score, WOMAC score, Trendelenburg sign, and limp between two groups. One hip of group A was revised by reason of dislocation at 8.3 years after surgery. One hip of group B was diagnosed with osteolysis and underwent a revision at 8.1 years after surgery. The Kaplan–Meier implants survivorship rates at the final follow‐up for all‐causes revisions in group A and group B were similar (96.7% [95% confidence interval, 90.5%–100%] and 96.2% [95% confidence interval, 89.0%–100%], respectively). Conclusions: The high hip center technique is a valuable alternative to achieve excellent midterm results for Crowe II–III developmental dysplasia of the hip. Further, between the groups with differing degrees of HHC, there were no significant differences in outcomes or survivorship in our study. Abstract : High hip center technique performing well in THA for Crowe II‐III DDH